Analyzing Black Hole Super-Radiance Emission of Particles/Energy from a Black Hole as a Gedankenexperiment to Get Bounds on the Mass of a Graviton - A. Beckwith (Advances in High Energy Physics)
Use of super-radiance in BH physics, so dE/dt<0 specifies conditions for a mass of a graviton being less than or equal to 1065 grams, allows for determing what role additional dimensions may play in removing the datum that massive gravitons lead to 3/4th the bending of light past the planet Mercury. The present document makes a given differentiation between super-radiance in the case of conventional BHs and Braneworld BH super-radiance, which may delineate whether Braneworlds contribute to an admissible massive graviton in terms of removing the usual problem of the 3/4th the bending of light past the planet Mercury which is normally associated with massive gravitons. This leads to a fork in the road between two alternatives with the possibility of needing a multiverse containment of BH structure or embracing what Hawkings wrote up recently, namely, a redo of the event horizon hypothesis as we know it.